Influence Of Controlled Breeding Techniques On Fertility And Plasma Macro-Minerals Profile In Conceiving And Non-Conceiving Anoestrus And Repeat Breeding Buffaloes - Savalia, K.K.; Dhami, A.J.; Patel, K.R.; Hadiya , K.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The study covered 50 postpartum buffaloes, 20 true anoestrus , 20 repeat breeders and 10 normal cyclic ones under field conditions with a view to evaluate oestrus response, conception rate and plasma profile of macro-minerals following use of different hormonal treatments. Ten anoestrus buffaloes each treated with CIDR and Ovsynch protocols with FTAI resulted in induction of ovulatory oestrus in all 10 and 8 buffaloes with conception in 4 and 3 animals at induced oestrus, respectively. Ten repeat breeding buffaloes with mature CL of mid-cycle treated with i/m injection of 25 mg PGF2α (Inj. Lutalyse) with FTAI caused ovulatory oestrus in 9 animals and conception in 4 buffaloes at induced estrus, while other ten repeat breeding buffaloes inseminated with simultaneous i/m Inj. of GnRH 20 μg (Inj. Receptal) resulted in conception in 3 animals. Among 10 normal cyclic control buffaloes, the first service conception was found in 3. The mean values of plasma calcium, phosphorus and magnesium in normal cyclic control group were 9.47 ± 0.31, 6.17 ± 0.18 and 2.96 ± 0.05 mg/dl, respectively, and only the phosphorus was significantly higher in conceived than non conceived buffaloes. There was no influence of periods of blood sampling (day 0 & 7 of treatment, Day of AI and day 21 post-AI) or conceived and non-conceived groups of CIDR and Ovsynch protocols on the three minerals. The plasma profile of none of the three minerals was influenced by days of sampling or pregnancy status in repeat breeder buffaloes under Mid-cycle PGF2α and AI + GnRH treatment groups and the values were close to those of normal cyclic group. It was thus concluded that the hormonal therapies improved conception rates in both anoestrus and repeat breeding buffaloes under field conditions, particularly with CIDR and Mid cycle PG injection, though they did not influence the plasma minerals profile significantly.